European Association of Urology Guidelines on Renal Cell Carcinoma: The 2022 Update - Ljungberg, Börje; Albiges, Laurence; Abu-Ghanem, Yasmin; Bedke, Jens; Capitanio, Umberto; Dabestani, Saeed; Fernández-Pello, Sergio; Giles, Rachel H; Hofmann, Fabian; Hora, Milan; Klatte, Tobias; Kuusk, Teele; et al. (European urology, 2022)
CONTEXT: The European Association of Urology (EAU) Renal Cell Carcinoma (RCC) Guideline Panel has prepared evidence-based guidelines and recommendations for the management of RCC. OBJECTIVE: To present a summary of the 2022 RCC guideline, which is based on a standardised methodology including systematic reviews (SRs) and provides transparent and reliable evidence for the management of RCC. EVIDENCE ACQUISITION: For the 2022 update, a new literature search was carried out with a cutoff date of May 28, 2021, covering the Medline, EMBASE, and Cochrane databases. The data search focused on randomised controlled trials (RCTs) and retrospective or controlled comparator-arm studies, SRs, and meta-analyses. Evidence synthesis was conducted using modified GRADE criteria as outlined for all the EAU guidelines. EVIDENCE SYNTHESIS: All chapters of the RCC guideline were updated on the basis of a structured literature assessment, and clinical practice recommendations were developed. The majority of the studies included were retrospective with matched or unmatched cohorts and were based on single- or multi-institution data or national registries. The exception was systemic treatment of metastatic RCC, for which there are several large RCTs, resulting in recommendations that are based on higher levels of evidence. CONCLUSIONS: The 2022 RCC guidelines have been updated by a multidisciplinary panel of experts using the highest methodological standards. These guidelines provide the most reliable contemporary evidence base for the management of RCC in 2022. PATIENT SUMMARY: The European Association of Urology panel for guidelines on kidney cancer has thoroughly evaluated the research data available to establish up-to-date international standards for the care of patients with kidney cancer.
Keywords: Kidney Neoplasms; Prognosis; Renal cell carcinoma; nádory ledvin; Carcinoma, Renal Cell; Guidelines; lidé; Management; Urology; Staging; Surgery; Systemic therapy; European Association of Urology; urologie; karcinom z renálních buněk; Diagnosis; Humans